Conceptions of food healthiness among nutrition and food science undergraduates: A mixed-methods study in a Spanish university - Ricard Celorio-Sardà; Mari Aguilera; Claudia Soar; Maria Clara Gómez; Oriol Comas-Basté; M. Carmen Vidal-Carou; Maria Clara de Moraes Prata Gaspar (PLoS ONE, 2026)
Understanding how future nutrition and food professionals conceptualize healthy food and eating is key to aligning university training and professional practice with public health and sustainability goals. This mixed-methods study explored how undergraduate students of Human Nutrition and Dietetics and of Food Science and Technology at a Spanish university define what makes foods healthy, and how these views differ by degree, gender, and year of study. The qualitative phase was based on two focus groups (n = 13) while the quantitative phase used a structured online questionnaire distributed across all academic years (n = 300). Students described healthy eating through moderation, variety, and nutrient balance, consistently elevating fruits, vegetables, legumes, nuts, and olive oil while positioning sugary drinks, sweets, and highly processed products as less healthy. Disciplinary contrasts emerged for animal-derived foods: Nutrition students judged red and processed meats more negatively than their peers in Food Science. With academic progression, perceptions tended to show a more favorable views of fish, olive oil, nuts, and fermented foods. A reduced reliance on claims such as “organic” or “GMO-free” was also observed. Women placed greater emphasis on plant-based choices, wholegrains, seasonality, proximity, and animal welfare, whereas men evaluated meats and alcoholic beverages more positively and expressed stronger trust in official quality seals. Agreement was highest with biomedical and holistic meanings of food, while endorsement of sociocultural definitions declined over the course of study. These findings provide insights into the evolving professional identities of future nutritionists and food technologists and support the importance to integrate more deeply sociocultural and sustainability perspectives into university curricula.